Analysis Of The Effectiveness Of Online-Based Personnel Administration Services In Company 3A Mobile Brigade Of The Lampung Regional Police - Ryan Setyabudi; Malik (Cita konsultindo, 2026)
The 3A Mobile Brigade Corps of the Lampung Regional Police has begun adopting an online-based administrative service system. This system is expected to improve the effectiveness of personnel administration by providing easier access, accelerating process flow, and reducing the risk of errors in data processing. This research design uses a qualitative approach with a descriptive method. qualitative descriptive analysis. The research design aims to describe and qualitatively analyze the Effectiveness of Administrative Services On Line Based Personnel at Company 3a Mobile Brigade of Lampung Regional Police. The results of the study show that the effectiveness of personal administrative services online-based at Company 3A Mobile Brigade of Lampung Regional Police, has been implemented according to dimension (1) time unit, the online-based administration system has help speed up the administrative service process, (2) output units, Service online-based administration is able to produce more structured documents and organized (3) quality of work, Online-based systems provide potential improving work quality with easy data access and increased accuracy document . The inhibiting aspects are (1) Time units, network limitations internet, technical problems with the system, and lack of familiarity with personnel towards technology is still a major obstacle in achieving efficiency maximum time. (2) Result Unit, Errors were still found in data entry, lack of automatic validation, and formatting discrepancies documents that hinder the achievement of optimal administrative results. (3) Quality of Work, limited technical training, resistance to change, and inadequate technological infrastructure remains a major challenge in maintaining the quality of personnel work.